The Perfect Combination: Semaglutide and Whole-Food Plant-Based Diet in Chronic Disease Care - Mulijono, Dasaad (Cardiology and Cardiovascular Medicine, 2025)
As the global burden of chronic disease escalates, clinicians are confronted with a pivotal decision: manage symptoms through costly, lifelong pharmaceutical interventions or address underlying causes via sustainable lifestyle changes. Semaglutide, a glucagon-like peptide-1 (GLP-1) receptor agonist, has rapidly emerged as a leading pharmacological solution, delivering notable short-term benefits in weight management and glycaemic control. However, these advantages often diminish upon discontinuation, accompanied by potential adverse effects, underscoring the need for sustainable therapeutic strategies. In contrast, whole-food plant-based diets (WFPBDs) offer a holistic, economically feasible approach that directly targets and rectifies the root metabolic dysfunctions driving chronic illnesses. At Bethsaida Hospital, Indonesia, under the pioneering leadership of Prof. Dasaad Mulijono (DM), we have innovatively integrated Semaglutide with WFPBD to leverage the strengths of both interventions. Prof. Dasaad Mulijono’s groundbreaking approach has resulted in remarkable clinical outcomes, including unprecedented remission rates for hypertension, substantial diabetes reversal, dramatic reductions in LDL cholesterol and restenosis following cardiac procedures, normalization of kidney function, and sustained weight management. These outcomes represent clinical success and a revolutionary shift toward lifestyle-driven reversal of chronic diseases. Further amplifying this success is our cutting-edge use of artificial intelligence (AI), which ensures enhanced patient adherence and personalized dietary management, underscoring Bethsaida Hospital's position as a global leader in the care of chronic diseases. This combined approach heralds a transformative era, redefining chronic diseases as manageable but reversible conditions, revolutionizing patient health outcomes and quality of life.